Sejarah Muncul dan Berkembangnya Islam di Bandung - Usman Supendi; Zahra Nur Azizah; Shaleh Afif Januri (UIN Sunan Gunung Djati Bandung, 2023)
AbstractAccording to several sources, Islam entered the archipelago in the 7th century AD. It is estimated that during the same period the spread of Islam began to spread massively to the archipelago, until in the 15th century AD Islam entered the West Java region through trade routes. The Bandung area, which at that time was still within the scope of the Galuh Kingdom, was converted to Islam during the time of Sunan Gunung Djati in 1530 AD. This Islamization process became the starting point for the spread and development of Islam in West Java. There is a lot of research on the development of Islam in various areas of West Java such as Garut, Tasikmalaya and even Cirebon, which was the starting point for the entry of Islam into West Java, which is inversely proportional to Bandung as the capital of West Java province. Not many people have conducted research. Therefore, the author is interested in writing about the development of Islam in Bandung in context. division of the Bandung region, such as how the spread of Islam in various regions of West, East, South and North Bandung. The method used is the historical method, which includes heuristics, criticism, interpretation and historiography. Based on research results, the entry of Islam in various regions in Bandung had different starting points for the spread of Islam in each region. Like North Bandung, it was spread through the spread of the preaching of Sunan Kudus and his followers and descendants, many of whom settled in the North Bandung area. Keywords: Islam, Bandung, Region AbstrakIslam masuk ke Nusantara menurut beberapa sumber pada abad ke-7 M. Diperkirakan masih dalam kurun waktu yang sama penyebaran Islam mulai masif ke daerah Nusantara, sampai pada abad ke-15 M Islam masuk wilayah Jawa Barat melalui jalur perdagangan.[1] Daerah Bandung yang pada saat itu masih dalam cakupan wilayah Kerajaan Galuh diislamkan pada masa Sunan Gunung Djati pada tahun 1530 Masehi.[2] Proses islamisasi ini menjadi titik awal penyebaran dan perkembangan islam Jawa Barat. Banyaknya penelitian mengenai perkembangan islam di berbagai daerah Jawa Barat seperti Garut, Tasikmalaya bahkan Cirebon yang menjadi titik awal masuknya islam ke Jawa Barat berbanding terbalik dengan Bandung sebagai ibukota provinsi Jawa Barat belum banyak yang melakukan penelitian untuk itu penulis tertarik menuliskan perkembangan islam di Bandung dalam konteks pembagian wilayah Bandung, seperti bagaimana sebaran masuknya islam di berbagai wilayah Bandung Barat,Timur,Selatan dan Utara. Metode yang digunakan adalah metode Sejarah, yang meliputi heuristik,kritik,interpretasi, dan historiograsi. Berdasarkan hasil penelitian masuknya islam di berbagai wilayah Bandung memiliki titik awal penyebaran islam yang berbeda dalam setiap wilayah. Seperti Bandung Utara disebarkan melalui penyebaran dakwah Sunan Kudus dan para pengikutnyanya serta keturunan yang banyak menetap wilayah Bandung utara. Kata kunci: Islam,Bandung,Wilayah